Keterkaitan densitas gizi, harga pangan, dan status gizi pada anak Sekolah Dasar Negeri (SDN) Pekayon 16 Pagi - Ekaningrum, Annisa Yuri; Sukandar, Dadang; Martianto, Drajat (Jurnal Gizi dan Pangan, 2017)
The purpose of this study was to analyze the relationship between energy density and food price, the relationship between nutrient density and food price, and the relationship between nutrient intake density and nutritional status using Body Mass Index for Age (BMI/A). Study design was cross-sectional and subjects were selected using stratified random sampling with proportional allocation. Population were 3rd, 4th, and 5th grade students atPekayon 16 Pagi Elementary School with the total subjects 158 students. Nutrient density was measured by NRF (Nutrient Rich Food) 9.3 index method. The study found that most of the subjects had adequate protein and energy intake density but low calcium, vitamin A, and vitamin C intake density. Energy, vitamin A, vitamin C, calcium, iron intake density were not correlated with BMI/A (p>0.05). Energy density was negatively correlated with  food price (r=-0.622). Nevertheless, nutrient density was positively correlated with  food price (r=0.614).